Chronic sun exposure is associated with distinct histone acetylation changes in human skin3. (27th May 2018) - Ding, S.; Chen, J.; Zeng, Q.; Lu, J.; Tan, L.; Guo, A.; Kang, J.; Yang, S.; Xiang, Y.; Zuo, C.; Huang, J.
Summary: Background: Photoageing is attributed to continuous sunlight or artificial ultraviolet exposure and manifests as clinical and histological changes in skin. Epigenetic changes have been found to be involved in the pathogenesis of photoageing. However, the underlying mechanisms are unclear. Objectives: To analyse histone modification patterns in sun‐exposed and nonexposed skin, and to identify the abnormally histone‐modified genes related to photoageing. Methods: Skin biopsies were collected from both the outer forearm (sun‐exposed area) and the buttock (sun‐protected area) in 20 healthy middle‐aged female volunteers. Global histone H3/H4 acetylation and H3K4/H3K9 methylation statuses were assessed by enzyme‐linked immunosorbent assay. Expression levels of histone acetyltransferases and histone deacetylases were measured by reverse‐transcriptase quantitative polymerase chain reaction (qPCR) and Western blot. Chromatin immunoprecipitation combined with DNA microarray (ChIP‐chip) assay with anti‐acetyl‐histone H3 antibody in a sun‐exposed pool (combining six sun‐exposed skin samples) and a nonexposed pool (combining six nonexposed skin samples) was conducted to explore the abnormally acetylated histone H3 genes related to photoageing; ChIP‐qPCR was then used to verify the results of ChIP‐chip. Results: We observed higher global histone H3 acetylation levels increased EP300 and decreased HDAC1 and SIRT1 expression in sun‐exposed skin compared with matched nonexposed skin. Furthermore, the ChIP‐chip assay showed that 227 genes displayed significant hyperacetylation of histone H3, and 81 genes displayed significant hypoacetylation of histone H3 between the two groups. Histone H3 acetylation levels on the promoters of PDCD5, ITIH5, MMP1 and AHR were positively correlated with the mRNA expression of the corresponding gene. Conclusions: Chronic sun exposure‐induced histone H3 hyperacetylation may play a critical role in the pathogenesis of skin photoageing. Abstract : What's already known about this topic? Ultraviolet radiation is the major contributor to the process of chronic photodamage in human skin. Aberrant epigenetic mechanisms are involved in the process of skin ageing. The epigenetic factors that trigger skin photoageing are poorly understood. What does this study add? Histone H3 acetylation status is changed in sun‐exposed skin. Altered expression levels of histone acetylation modifier genes such as EP300, HDAC1 and SIRT1 may contribute to the aberrant histone H3 acetylation pattern in sun‐exposed skin. In total, 227 genes displayed significant histone H3 hyperacetylation and 81 displayed significant histone H3 hypoacetylation in sun‐exposed skin. What is the translational message? Histone H3 acetylation is implicated in regulating the expression of key photoageing‐related genes in skin. Linked Comment:  Gunn. Br J Dermatol 2018;179 :10–11 . Plain language summary available online Respond to this article